Stomatal regulation prevents plants from critical water potentials during drought: Result of a model linking soil–plant hydraulics to abscisic acid dynamics - Wankmüller, Fabian J. P.; Carminati, Andrea (Ecohydrology, 2022)
Understanding stomatal regulation during drought is essential to correctly predict vegetation‐atmosphere fluxes. Stomatal optimization models posit that stomata maximize the carbon gain relative to a penalty caused by water loss, such as xylem cavitation. However, a mechanism that allows the stomata to behave optimally is unknown. Here, we introduce a model of stomatal regulation that results in similar stomatal behaviour without presupposing an optimality principle. By contrast, the proposed model explains stomatal closure based on a well‐known component of stomatal regulation: abscisic acid (ABA). The ABA level depends on its production rate, which is assumed to increase with declining leaf water potential, and on its degradation rate, which is assumed to increase with assimilation rate. Our model predicts that stomata open until the ratio of leaf water potential to assimilation rate, proportional to ABA level, is at a minimum. As a prerequisite, the model simulates soil–plant hydraulics and leaf photosynthesis under varying environmental conditions. The model predicts that in wet soils and at low vapour pressure deficit (VPD), when there is no water limitation, stomatal closure is controlled by the relationship between photosynthesis and stomatal conductance. In dry soils or at high VPD, when the soil hydraulic conductivity limits the water supply, stomatal closure is triggered by the sharp decline in leaf water potential as transpiration rate increases. Being adaptive to changing soil and atmospheric conditions, the proposed model can explain how plants are enabled to avoid critical water potentials during drought for varying soil properties and atmospheric conditions.